Mosquito identification, surveillance and trapping methods for area-wide integrated mosquito management in the European area - Vasquez Christodoulou, Marlen (My University, 2026)
▪ Biology, morphology, ecology and behavior of mosquito ▪ Mosquito trapping and surveillance technology ▪ Methods for collection, handling and storage of mosquito samples ▪ Methods of mosquito identification and classification Dr Martin Geiger, Dr Francis Schaffner and Dr Dusan Petric